Latest development on RNA-based drugs and vaccines. (9th April 2018) - Lundstrom, Kenneth
Drugs and vaccines based on mRNA and RNA viruses show great potential and direct translation in the cytoplasm eliminates chromosomal integration. Limitations are associated with delivery and stability issues related to RNA degradation. Clinical trials on RNA-based drugs have been conducted in various disease areas. Likewise, RNA-based vaccines for viral infections and various cancers have been subjected to preclinical and clinical studies. RNA delivery and stability improvements include RNA structure modifications, targeting dendritic cells and employing self-amplifying RNA. Single-stranded RNA viruses possess self-amplifying RNA, which can provide extreme RNA replication in the cytoplasm to support RNA-based drug and vaccine development. Although oligonucleotide-based approaches have demonstrated potential, the focus here is on mRNA- and RNA virus-based methods. Lay abstract: Drug development has suffered from inefficiency, side effects and high costs. For this reason novel approaches for drug discovery are of great importance. RNA-based methods provide the advantage of targeting 'production' of drugs to diseased cells and vaccines to immune response-stimulating cells. RNA drugs have demonstrated therapeutic efficacy in eye and heart diseases and in various cancers in clinical trials. Likewise, RNA-based vaccines have provided protection against challenges with lethal doses of viruses such as Ebola and cancer cells in animal models.